Very high‐frequency oscillations: Novel biomarkers of the epileptogenic zone. Issue 2 (August 2017) - Brázdil, Milan; Pail, Martin; Halámek, Josef; Plešinger, Filip; Cimbálník, Jan; Roman, Robert; Klimeš, Petr; Daniel, Pavel; Chrastina, Jan; Brichtová, Eva; Rektor, Ivan; Worrell, Gregory A.; et al.
Abstract : Objective: In the present study, we aimed to investigate depth electroencephalographic (EEG) recordings in a large cohort of patients with drug‐resistant epilepsy and to focus on interictal very high‐frequency oscillations (VHFOs) between 500Hz and 2kHz. We hypothesized that interictal VHFOs are more specific biomarkers for epileptogenic zone compared to traditional HFOs. Methods: Forty patients with focal epilepsy who underwent presurgical stereo‐EEG (SEEG) were included in the study. SEEG data were recorded with a sampling rate of 25kHz, and a 30‐minute resting period was analyzed for each patient. Ten patients met selected criteria for analyses of correlations with surgical outcome: detection of interictal ripples (Rs), fast ripples (FRs), and VHFOs; resective surgery; and at least 1 year of postoperative follow‐up. Using power envelope computation and visual inspection of power distribution matrixes, electrode contacts with HFOs and VHFOs were detected and analyzed. Results: Interictal very fast ripples (VFRs; 500–1, 000Hz) were detected in 23 of 40 patients and ultrafast ripples (UFRs; 1, 000–2, 000Hz) in almost half of investigated subjects (n = 19). VFRs and UFRs were observed only in patients with temporal lobe epilepsy and were recorded exclusively from mesiotemporal structures. The UFRs were more spatially restricted in the brain than lower‐frequency HFOs. When compared to R oscillations, significantly better outcomes were observed in patients with a higher percentage of removed contacts containing FRs, VFRs, and UFRs. Interpretation: Interictal VHFOs are relatively frequent abnormal phenomena in patients with epilepsy, and appear to be more specific biomarkers for epileptogenic zone when compared to traditional HFOs. Ann Neurol 2017;82:299–310